2019
DOI: 10.3748/wjg.v25.i31.4405
|View full text |Cite
|
Sign up to set email alerts
|

Overview and comparison of guidelines for management of pancreatic cystic neoplasms

Abstract: Pancreatic cysts are identified at an increasing frequency. Although mucinous cystic neoplasms represent a pre-malignant condition, the majority of these lesions do not progress to cancer. Over the last 10 years several societies have established guidelines for the diagnosis, initial evaluation and surveillance of these lesions. Here we provide an overview of five commonly used guidelines: 2015 American Gastroenterological Association, 2017 International Association of Pancreatology, American College of Gastro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 23 publications
0
51
0
3
Order By: Relevance
“…Despite these improvements, the most recent International Consensus Guidelines (ICG) continue to contribute to unnecessary pancreatic resections because morphologic imaging features on CT and/or MRI are still inaccurate for assessing dysplasia [14,16,17]. A multi-institutional study by Wilson et al, which included 324 patients, found that only 44% of the specimens resected had LGD [18].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these improvements, the most recent International Consensus Guidelines (ICG) continue to contribute to unnecessary pancreatic resections because morphologic imaging features on CT and/or MRI are still inaccurate for assessing dysplasia [14,16,17]. A multi-institutional study by Wilson et al, which included 324 patients, found that only 44% of the specimens resected had LGD [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, they do not consider solid papillary neoplasms, neuroendocrine tumours and main duct IPMN without branch duct involvement. 23 Like the IAP consensus guidelines, they also recommended surgical resection for main duct and mixed main and branch duct IPMNs and MCNs. However, they differed from the Sendai and Fukuoka guidelines in that the AGA algorithm incorporates all other PCLs in addition to branch duct IPMNs.…”
Section: Guidelinesmentioning
confidence: 99%
“…27 They target those patients found incidentally to have PCLs but lack a strong family history and genetic mutations which may result in pancreatic cancer. 23 These guidelines are unique in their diagnosis and management of serous cystadenomas and pseudocysts and their recommendations for surveillance cessation. 23,27 Recent diagnostic advances Endoscopic ultrasound and cyst fluid analysis EUS is generally considered the most sensitive diagnostic modality for malignant PCLs.…”
Section: American College Of Gastroenterology (Acg) Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…La neoplasia quística mucinosa del páncreas (NQMP) es un tumor infrecuente, que afecta predominantemente a mujeres (90-95 %), afectando especialmente entre la quinta y séptima década de la vida; cuyo descubrimiento suele ser incidental por cortes imagenológicos del abdomen. Por lo general, son lesiones solitarias, sin compromiso del conducto pancreático principal; poco sintomáticas y asociadas a malignidad en un 10 a 40 % de los casos, dependiendo en especial de su tamaño (Jorba et al, 2008;Troncoso et al, 2015;Burk et al, 2018; European Study Group on Cystic Tumours of the Pancreas, 2018;van Huijgevoort et al, 2019;Hurtado-Pardo et al, 2019;Hasan et al, 2019).…”
Section: Introductionunclassified